Cytotoxicity of Contrast Media Iohexol on IL-1beta stimulated Bovine Chondrocytes - HONG, G.; HWANG, Y.; KIM, G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of this study was to determine the cytotoxic and metabolic effects of iohexol on cultured bovine chondrocytes in clinical dose. Chondrocytes were exposed to 50%, 25% and 12.5% iohexol and 50% mannitol for 2 hours. Cell proliferation, apoptosis and necrosis were analyzed. Real time PCR was performed for aggrecan, collagen type I and II gene expression. Cells in alginate beads stimulated by interleukin-1β (IL-1β) were analyzed for cytotoxicity. MTT assay showed that 50% iohexol inhibited the proliferation of cells at 2 hours culture period. Propidium iodide results showed significantly higher dead cells at 50% iohexol compared to control, however PCR results revealed that chondrogenic gene were not affected. Cells in alginate beads stimulated with IL-1β showed significantly higher percentage of dead cells at 50% iohexol exposure (p<0.05). These results suggested that iohexol has a cytotoxicity on chondrocytes and this cytotoxic effect possibly increased in inflammatory joint diseases.